Effects of Native Arbuscular Mycorrhizae Isolated on Root Biomass and Secondary Metabolites of Salvia miltiorrhiza Bge - Wu, Yan-Hong; Wang, Hai; Liu, Min; Li, Bo; Chen, Xin; Ma, Yun-Tong; Yan, Zhu-Yun (Frontiers in Plant Science, 2021)
Arbuscular mycorrhiza fungi (AMFs) are a group of soil-dwelling fungi that form symbiotic associations with land plants, which mediate the secondary metabolism and production of active ingredients in aromatic and medicinal plants. At present, there is no research on the effects of Salvia miltiorrhiza Bge. inoculation with native AMFs on the growth and the content of secondary metabolites. In this study, S. miltiorrhiza was inoculated with eight species of AMF (Glomus formosanum; Gl. tenebrosum; Septoglomus constrictum; Funneliformis geosporum; Rhizophagus manihotis; Ambispora gerdemanii; Acaulospora laevis; Ac. tuberculata), in greenhouse cultivation conditions to investigate the influence of AMFs inoculation biomass and secondary metabolites under greenhouse conditions in the root of S. miltiorrhiza. The results showed that the formation rate of mycorrhiza was between 54.83% and 86.10%. Except for Acaulospora laevis treatment, the biomass of the underground part of the other treatment groups was effectively increased, and the fresh weight and dry weight of the plant inoculated with Funneliformis geosporum were increased by 86.76% and 86.95%, respectively. Specifically, AMFs treatment had a greater impact on phenolic acids. In addition to inoculation with Funneliformis geosporum which significantly reduced the content of total phenolic acids, the other treatments effectively increased the content of total phenolic acids, among which Gl. formosanum, Ambispora gerdemanii, and Ac. tuberculata treatments all reached significant levels. Most AMF-plant symbiosis facilitated the accumulation of phenolic acids in the secondary metabolites of S. miltiorrhiza (except Acaulospora laevis treatment). This study showed that S. miltiorrhiza participating in different native AMF varieties had different degrees of affinity. It is necessary to select effective AMF species to promote the growth of S. miltiorrhiza and improve the quality and yield of its root.